The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1051/matecconf/201928202091
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnesium oxide boards used as sheathing in exterior walls

Abstract: Sheathing boards based on magnesium oxide (MgO) became very popular in the Danish market around the year 2010. However, it was realized a few years later that they condensed humidity from ambient air. The leakage from the boards led to severe problems with corrosion of metallic components and moisture uptake and degradation of wooden members. The boards have been banned from use in the Danish market since 2015, while damage cases valuing around 370 million EUR still need to be reconciled [1]. The binder in MgO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A study by Rode et al [29] also confirms that when relative humidity exceeds 84%, MgO boards start to absorb excessive amounts of moisture from the surrounding air. As such higher levels of humidity are typical in the places where exterior lining is to be used, it can be concluded that MgO boards are not a suitable product for this purpose.…”
Section: Moisture Propertiesmentioning
confidence: 82%
“…A study by Rode et al [29] also confirms that when relative humidity exceeds 84%, MgO boards start to absorb excessive amounts of moisture from the surrounding air. As such higher levels of humidity are typical in the places where exterior lining is to be used, it can be concluded that MgO boards are not a suitable product for this purpose.…”
Section: Moisture Propertiesmentioning
confidence: 82%
“…Exposure to high RH removes influence from the changing pH of the water solution which is dependent on the mix composition. Furthermore, it is more representative of conditions in applications where MOC is currently used such as a sheathing board in wall systems (Aiken et al 2020;Wøhler Nielsen et al 2019) where they can be exposed to periods of high RH rather than immersed in water. Fig.…”
Section: Moisture Resistancementioning
confidence: 99%
“…It is also susceptible to moisture which causes transformation of its main phases and a subsequent loss of strength (Deng 2003;Mitina et al 2016;Wang et al 2019). Despite these issues MOC has many niche applications including grinding wheels, lightweight wall panels, floor tiles and decorative panels (Aiken et al 2020(Aiken et al , 2021Chau and Li 2008;Li and Chau 2008;Wøhler Nielsen et al 2019;Zhou and Li 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, complete flat roofs were difficult to execute with sufficient quality and the roofing materials were not durable for this solution. Therefore, many roofs leaked and resulted in expensive renovation projects and claims corresponding to 4 % of the contract sum for dwellings with flat roofs (Bunch- Nielsen, 2019).…”
Section: Case 1: Flat Roofsmentioning
confidence: 99%
“…The binder in MgO board is formed by a chemical reaction between MgO and MgCl2. Boards containing MgSO4 were later introduced to the market because of the less hygroscopic behavior of MgSO4 compared to MgCl2 but they showed not to be a feasible alternative in Denmark and countries with a similar humid climate (Wøhler Nielsen et al, 2019).…”
Section: Case 2: Magnesium Oxide Containing Boards As Wind Barriermentioning
confidence: 99%